Ion track diameter in fullerene C70 thin film using Raman active vibrational modes of C70 molecule. (January 2016) - Sharma, Pooja; Singhal, R.; Vishnoi, R.; Kaushik, R.; Banerjee, M.K.; Avasthi, D.K.; Ganesan, V.
Abstract: The effect of energy deposition in fullerene C70 (∼150 nm) thin film deposited by resistive heating method on glass, quartz and silicon substrates was investigated. The samples were irradiated with 90 MeV Ni ion beam at the fluences ranging from 1 × 10 12 to 3 × 10 13 ions/cm 2 . The pristine and Ni ion irradiated samples were examined for morphological and optical changes by Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), UV–visible absorption spectroscopy and Raman spectroscopy. After ion irradiation, bigger grains are shown on surface as revealed by SEM analysis indicating the agglomeration of the smaller particles into bigger particles at the surface. UV–visible absorption studies reflect that the direct band gap of the film decreases with increase in ion fluence. At higher fluence, fullerene C70 is transformed into amorphous carbon (a-C) which is confirmed by Raman spectroscopy. The damage cross-section (σ) and radius of the damaged cylindrical zone (r) are approximated to be ∼1.72 × 10 −13 cm 2 and ∼2.3 nm, respectively using Raman active vibrational modes. Highlights: Thin film of fullerene C70 has been synthesized by thermal evaporation method in high vacuum. Fullerene C70 films were irradiated with 90 MeV Ni ion beams using Pelletron Accelerator. The nano channel (ion tracks) are created in the fullerene film by ion irradiation. The radius of ion track has been found to be 2.3 nm using Raman Spectroscopy. Change in the band gap of fullerene C70 with ion irradiation as well as surface properties has also been investigated.